RICE STRAW AND HUSK OIL SLUDGE FOR PROCESSING THROUGH THE USE OF LIGNOSULFONATE AS A BINDER WITH ACTIVATED CHARCOAL - N. O. Appazov; B. M. Diyarova; B. M. Bazarbayev; T. Assylbekkyzy; S. A. Kanzhar; B. Zh. Dzhiembaev (Academic Scientific Journal of Chemistry, 2021)
This article examines the effect of lignosulfonate binding of rice waste to oil waste to obtain activated carbon. Lignosulfonate was added to the mixture to produce briquetted activated carbon by processing rice residue (husk and straw) and oil sludge together. The mixture was carbonized and activated in a BR-12 NFT series hightemperature vacuum tube furnace with a length of 300 mm and a diameter of 60 mm and a heating section length of 200 mm in a quartz glass tube. Briquettes obtained by adding rice waste (husks and straw), oil sludge and lignosulfonate were placed in the kiln. Carbonation was carried out at a temperature of 500°C, activation was carried out at a temperature of 850°C in a ratio of 2: 1 with water vapor. The effect of the relationship of the addition of lignosulfonate binder to rice residue and oil sludge on the product properties was studied. The optimal ratio of cotreatment of the mixture was found in the ratio of rice residue: oil sludge: lignosulfonate = 9: 1: 2 (by weight). The adsorption activity of the obtained product on iodine, the total volume of pores on water, the mass fraction of moisture, the adsorption activity on methylene blue and the bulk density were studied. Activated carbon obtained from both rice straw and rice husk has high sorption properties. According to the results of experimental studies, activated carbon obtained by adding lignosulfonate to rice straw and oil sludge in a ratio of 9: 1: 2 corresponds to the brands BAС-A, WAC, BAC-Au